Polarizing element, manufacturing method thereof, and head-up display device
The use of a grid structure with transparent inorganic materials and nano-printing techniques for vehicle head-up displays addresses heat resistance and manufacturing challenges, ensuring effective heat dissipation and cost efficiency in polarized elements.
Patent Information
- Application Number
- JP2021164825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-23
- Filing Date
- 2021-10-06
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-06-25
AI Technical Summary
Existing wire grid polarized elements used in vehicle head-up displays lack sufficient heat resistance and heat dissipation, leading to potential deterioration and failure due to high temperatures, especially in automotive environments, and are costly to manufacture.
A polarized element with a grid structure formed from transparent inorganic materials, featuring protrusions on a substrate, which is manufactured using nano-printing techniques, includes an optical function film and a protective coating, enhancing heat dissipation and reducing manufacturing complexity.
The solution provides polarized elements with excellent heat resistance and heat dissipation, enabling reliable operation in high-temperature environments while reducing production costs and complexity.
Smart Images

Figure 0007625503000001 
Figure 0007625503000002 
Figure 0007625503000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing element having good polarization characteristics, excellent heat dissipation properties and low manufacturing costs, a method for manufacturing a polarizing element, and a head-up display device having excellent polarization characteristics and heat resistance. [Background technology]
[0002] In recent years, many head-up display devices for vehicles have been developed that display images on semi-transparent plates (hereinafter collectively referred to as "display surfaces") such as the windshield or a combiner of a vehicle. A head-up display device for vehicles is, for example, an image display device that is disposed on the dashboard of a vehicle, projects image light onto the windshield, and displays driving information as a virtual image. Since the driver can simultaneously view the virtual image and the scenery through the windshield, there is an advantage that there is less movement of the line of sight compared to conventional display devices such as liquid crystal displays that are installed outside the range of the windshield.
[0003] However, in the above-mentioned head-up display device, since the display image is emitted from below toward the windshield surface (upward), sunlight can enter in the opposite direction to the emission direction of the display image and enter the display element. In many head-up display devices, a reflector is provided to reflect and enlarge the display image in order to meet the demand for compactness and to enlarge the display image, and in such cases, sunlight entering the head-up display is concentrated near the display element, which can cause deterioration or failure of the display element due to heat.
[0004] Therefore, a technology has been developed to provide a reflective polarizing element in a head-up display in order to prevent sunlight from entering the display element. For example, Patent Document 1 discloses a head-up display in which a reflective polarizing element (wire grid polarizer) is provided between a reflector and a display element.
[0005] Here, examples of the polarizing element provided in the head-up display include a polarizing element made of a birefringent resin, a wire-grid type polarizing element in which a plurality of conductors (thin metal wires) extend in parallel on a transparent substrate, and a polarizing element made of cholesteric phase liquid crystal. Among these, wire-grid type polarizing elements are often used as elements having excellent polarization characteristics. In a wire-grid polarizing element, a wire grid is formed in which conductor wires made of metal or the like are arranged in a lattice shape at a specific pitch, and by setting the arrangement pitch of the wire grid to a pitch (half or less) smaller than the incident light (for example, the wavelength of visible light), it is possible to reflect most of the light of the electric field vector component oscillating parallel to the conductor wire and transmit most of the light of the electric field vector component perpendicular to the conductor wire. As a result, it can be used as a polarizing element that produces single polarized light, and can reflect and reuse the light that is not transmitted, which is desirable from the viewpoint of effective use of light.
[0006] As an example of such a wire grid polarizer, Patent Document 2 discloses a wire grid polarizer including a resin substrate having grid-shaped protrusions, a dielectric layer provided so as to cover the grid-shaped protrusions of the resin substrate and at least a portion of their side surfaces, and metal wires provided on the dielectric layer. Patent Document 3 discloses a wire grid polarizer having a substrate made of a resin or the like having a concave-convex structure on its surface extending in a specific direction, and a conductor arranged so as to be concentrated on one side of the convex portions of the concave-convex structure, in which the pitch, which is the distance between two adjacent convex portions, and the height of the convex portions are adjusted in a cross-sectional view perpendicular to the extension direction of the concave-convex structure. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-72507 A [Patent Document 2] JP 2008-83657 A [Patent Document 3] JP 2017-173832 A Summary of the Invention [Problem to be solved by the invention]
[0008] Generally, the temperature environment required for devices used in a vehicle is -40 to 105°C. However, when considering use in a high temperature environment, such as a head-up display mounted on the dashboard of a vehicle in summer, high heat resistance and heat dissipation are required. However, the techniques of Patent Documents 1 to 3 are basically wire grid polarizers using a resin substrate, and the wire grid polarizer itself does not have sufficient heat resistance and heat dissipation. In addition, the wire grid polarizers using the above-mentioned resin substrate are generally used by attaching them to a glass substrate using double-sided tape (OCA: Optically Clear Adhesive), but there are problems such as stray light due to undulation of the film substrate and warping of the polarizing film due to heat, and further improvements have been required.
[0009] Furthermore, in the wire-grid polarizer of Patent Document 3, a lattice-like unevenness is formed on the surface of the substrate during manufacturing, which makes it difficult to select a material taking into account processability and heat dissipation properties, and also makes it difficult to achieve both polarization properties and heat dissipation properties.
[0010] Furthermore, conventional wire grid polarizers have problems such as high manufacturing costs and being unsuitable for mass production because the uneven surface shape is generally formed by photolithography or etching techniques.
[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a polarizing element and a manufacturing method thereof that have good polarization characteristics, excellent heat dissipation properties, and low manufacturing costs. Another object of the present invention is to provide a head-up display device that has excellent polarization characteristics and heat resistance. [Means for solving the problem]
[0012] As a result of intensive research to solve the above problems, the inventors have found that by forming the substrate of the polarizing element from a transparent inorganic material and forming the grid structure having a concave-convex structure to have a base portion provided along the surface of the substrate and protrusions protruding from the base portion in a lattice shape, it is possible to improve the heat dissipation effect while maintaining excellent polarization characteristics. Furthermore, since the above-mentioned grid structure has a base portion and protrusions, which can be formed by a technique such as nanoimprinting, it is possible to reduce the manufacturing cost and enable mass production compared to the case of using photolithography or etching.
[0013] The present invention has been made based on the above findings, and the gist of the present invention is as follows. (1) a substrate made of a transparent inorganic material; a grid structure made of a transparent material and having a base portion provided along a surface of the substrate and protrusions protruding in a grid shape from the base portion; an optically functional film formed on the protrusion, the optically functional film being an absorptive film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorptive film and the reflective film; A polarizing element comprising: (2) The polarizing element according to (1) above, wherein the base portion has a thickness of 1 nm or more. (3) The polarizing element described in (1) or (2) above, characterized in that the shape of the protrusion when viewed in a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element is rectangular, trapezoidal, polygonal, or elliptical. (4) The polarizing element according to any one of (1) to (3) above, wherein the optically functional film is formed at least on the tips of the protrusions. (5) The polarizing element according to any one of (1) to (4) above, wherein the optically functional film is not formed on the base portion. (6) The polarizing element according to (4) or (5) above, wherein the optically functional film is formed on the tip of the protrusion and part of the side surface of the protrusion. (7) The polarizing element described in (6) above, characterized in that the optical functional film formed on a portion of the side surface of the protrusion is formed over an area covering 10% or more of the height of the protrusion. (8) The polarizing element according to any one of (1) to (7) above, wherein the inorganic material constituting the substrate is different from the material constituting the grid structure. (9) The polarizing element according to any one of (1) to (8) above, further comprising a protective film formed so as to cover at least the surface of the optically functional film. (10) The polarizing element according to (9) above, characterized in that the protective film includes a water-repellent coating or an oil-repellent coating. (11) The polarizing element according to any one of (1) to (10) above, wherein the optically functional film is made of a multilayer film having at least the absorbing film and the reflective film. (12) The polarizing element according to (11) above, wherein the optically functional film further comprises a dielectric film between the reflective film and the absorbing film. (13) forming a grid structure material made of a transparent material on a substrate made of an inorganic material; forming a grid structure having a base portion provided along a surface of a substrate and protrusion portions protruding in a lattice pattern from the base portion by nanoimprinting the grid structure material; and forming, on the protrusion, an optically functional film consisting of an absorbing film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorbing film and the reflective film. (14) The method for producing a polarizing element according to (13) above, wherein the step of forming the optically functional film comprises depositing films alternately from a plurality of directions on the protrusions by sputtering or vapor deposition. (15) A head-up display device, comprising the polarizing element according to any one of (1) to (14) above. (16) The head-up display device according to (15) above, further comprising a heat dissipation member provided around the polarizing element. Effect of the Invention
[0014] According to the present invention, it is possible to provide a polarizing element having good polarization characteristics, excellent heat dissipation properties, and a manufacturing method for a polarizing element, which is low in manufacturing cost. Also, according to the present invention, it is possible to provide a head-up display device having excellent polarization characteristics and heat resistance. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a diagram illustrating one embodiment of the polarizing element of the present invention, where (a) is a cross-sectional view that illustrates the polarizing element of the present invention, and (b) is a top view that illustrates the polarizing element of the present invention. [Diagram 2] 1A to 1C are diagrams showing schematic examples of cross-sectional shapes of protrusions of a grid structure of a polarizing element of the present invention. [Diagram 3] 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of a polarizing element of the present invention. [Figure 4] 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of a polarizing element of the present invention. [Diagram 5] 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of a polarizing element of the present invention. [Figure 6] FIG. 1(a) is a cross-sectional view that shows a schematic representation of one embodiment of a polarizing element of the present invention, and FIG. 1(b) is a cross-sectional view that shows a schematic representation of another embodiment of a polarizing element of the present invention. [Figure 7] FIG. 1 is a perspective view showing a schematic diagram of an embodiment of a polarizing element of the present invention. [Figure 8]Photographs of one embodiment of the polarizing element of the present invention taken at magnification using a scanning electron microscope (SEM), where (a) is a top view, (b) is a cross-sectional view, (c) is a further enlarged view of (b), and (d) is a further enlarged view of (c). [Figure 9] FIG. 1 is a diagram for explaining one embodiment of a manufacturing method for a polarizing element of the present invention, in which (a) shows a state in which a grid structure material is formed on a substrate, (b) shows a state in which the grid structure material is nanoimprinted, (c) shows a state in which the grid structure is formed on a substrate, and (d) shows a state in which an optically functional film is formed on protrusions of the grid structure, and further, a protective film is formed on the surfaces of the grid structure and the optically functional film. [Figure 10] FIG. 1 is a diagram for explaining an example of a conventional method for manufacturing a polarizing element, in which (a) shows a state in which a metal material and an optically functional film material are formed on a substrate, (b) shows a state in which a resist mask is formed on the optically functional film material, (c) shows the state after etching has been applied to the metal material and the optically functional film material, (d) shows the state after the resist mask has been peeled off, and (e) shows the state in which a protective film has been formed on the surface. [Figure 11] FIG. 1 shows an example of a process for fabricating a mold for nanoimprinting of a grid structure material, where (a) shows a metal material formed on a substrate, (b) shows a resist mask formed on the metal material, (c) shows the metal material after etching, (d) shows the resist mask after peeling, and (e) shows a release coating formed on the surface of the obtained mold. [Figure 12] 1 is a cross-sectional view that illustrates a schematic diagram of an embodiment of a head-up display device according to the present invention. [Figure 13] FIG. 11 is a cross-sectional view that illustrates a schematic diagram of another embodiment of a head-up display device according to the present invention. [Figure 14] 13 is a graph comparing optical characteristics when the material of the grid structure is changed in Example 2. [Figure 15] 13 is a graph comparing optical characteristics when the thickness of a base portion of a grid structure is changed in Example 2. [Figure 16] 13 is a graph comparing optical characteristics when the height of protrusions of a grid structure is changed in Example 2. [Figure 17] 13 is a graph comparing optical characteristics when the thickness of an absorbing film formed on a protrusion is changed in Example 2. [Figure 18] 13 is a graph comparing optical characteristics when the material of the absorbing film formed on the protrusion is changed in Example 2. [Figure 19] 13 is a graph comparing optical characteristics when the width of the absorbing film formed on the protrusion is changed in Example 2. [Figure 20] 13 is a graph comparing optical characteristics when the state of formation of an absorbing film formed on a protrusion is changed in an example. [Figure 21] 11 is a graph comparing optical characteristics when the thickness of a reflective film formed on a protrusion is changed in an example. [Figure 22] Graph (a) is a graph comparing the optical properties when the combination of films in the optically functional film formed on the protrusion in the embodiment is changed, and graph (b) is an easy-to-understand graph showing only the CR results from the optical properties shown in (a). [Figure 23] Photograph (a) is an enlarged photograph taken with a scanning electron microscope (SEM) of a cross section of an actually produced polarizing element of the present invention, and photograph (b) is a further enlarged photograph of a portion of photograph (a). [Figure 24] 1 is a graph comparing optical properties before and after a high-temperature test in an embodiment. [Diagram 25] 1A to 1C are diagrams showing schematic examples of cross-sectional shapes of recesses between protrusions in a base portion of a grid structure of a polarizing element of the present invention. [Figure 26] 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of a polarizing element of the present invention. [Figure 27]Graph (a) is a graph comparing the optical characteristics when the range of the reflective film formed on the tip and part of the side of the protrusion covering the protrusion (the ratio of the height range covered by the optically functional film to the height of the protrusion) in the embodiment is changed, and graph (b) is a graph comparing the contrast when the height range of the reflective film formed on the tip and part of the side of the protrusion covering the protrusion is changed in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the polarizing element of the present invention and embodiments of the head-up display of the present invention will be specifically described with reference to the drawings as necessary. Note that, for the convenience of description, some of the members disclosed in Figs. 1 to 13 are shown diagrammatically at a scale and in a shape different from the actual ones.
[0017] <Polarizing element> First, one embodiment of the polarizing element of the present invention will be described. As shown in Figures 1(a) and (b), the polarizing element of the present invention is a polarizing element 1 comprising a substrate 10 made of a transparent inorganic material, a grid structure 20 made of a transparent material and having a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding in a grid pattern from the base portion 21, and an optically functional film 30 formed on the protrusions 22 and consisting of an absorbing film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorbing film and the reflective film.
[0018] The substrate 10 of the polarizing element 1 is made of an inorganic material having high thermal conductivity, and the grid structure 20 having a concave-convex structure has a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding in a lattice shape from the base portion 21, so that the grid structure 20 can be made of the inorganic substrate 10 and the thin base portion 21, and as a result of obtaining an advantageous effect in terms of thermal resistance, excellent polarization characteristics can be realized while improving the heat dissipation effect. As described above, the grid structure 20 has the base portion 21 and the protrusions 22, which can be formed by a technique such as nanoimprinting, and therefore the cost and complexity of the manufacturing can be reduced compared to the case of using photolithography or etching. On the other hand, conventional film-type organic polarizing plates use a large amount of organic materials and have thick substrates (base films), double-sided tapes (OCA: Optically Clear Adhesive), and grid structures, and are therefore considered to have inferior heat dissipation and heat resistance compared to the polarizing element of the present invention.
[0019] Hereinafter, components of one embodiment of the polarizing element of the present invention will be described. (substrate) A polarizing element 1 of the present invention includes a substrate 10, as shown in FIG. The substrate 10 is made of a transparent inorganic material. By using an inorganic material for the substrate 10, the thermal conductivity of the substrate 10 is increased, and therefore the heat dissipation property of the polarizing element 1 can be improved. In this specification, "transparent" means that the transmittance of light of wavelengths belonging to the bands of use (visible light and infrared light) is high, for example, the transmittance of the light is 70% or more. The polarizing element 1 uses a material that is transparent to light of the bands of use, and therefore does not adversely affect the polarization characteristics, light transmittance, etc. of the polarizing element 1.
[0020] Examples of materials for the substrate 10 include various types of glass, quartz, crystal, sapphire, etc. Among these, the material for the substrate 10 preferably has a thermal conductivity of 1.0 W / m·K or more, and more preferably has a thermal conductivity of 8.0 W / m·K or more, because this provides better heat dissipation properties.
[0021] The shape of the substrate 10 is not particularly limited and can be appropriately selected depending on the performance required for the polarizing element 1. For example, it can be configured to have a plate shape or a curved surface. In order not to affect the polarization characteristics of the polarizing element 1, the surface of the substrate 10 can be a flat surface. Furthermore, the thickness TS of the substrate 10 is not particularly limited, and can be within the range of, for example, 0.3 to 10.0 mm.
[0022] (Grid Structure) In embodiment 1 of the polarizing element of the present invention, as shown in Figure 1(a), the substrate 10 is further provided with a grid structure 20 made of a transparent material and having a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding in a grid pattern from the base portion 21. The grid structure 20 can obtain desired polarization characteristics by providing an optically functional film 30, which will be described later, on the lattice-shaped protrusions 22 formed on the surface.
[0023] When the optical function film 30 described later has an absorbing function, the light incident from the surface on which the protrusions 22 of the grid structure 20 are formed is partially absorbed and attenuated when passing through the optical function film 30. When the optical function film 30 has a reflective function, the incident light is partially reflected when passing through the optical function film 30. Of the light transmitted through the optical function film 30, light having an electric field component in a direction (transmission axis direction) perpendicular to the longitudinal direction (absorption axis direction or reflection axis direction) of the protrusions 22 passes through the polarizing element 1 with high transmittance. On the other hand, of the light transmitted through the optical function film 30, light having an electric field component in a direction (absorption axis direction or reflection axis direction) parallel to the longitudinal direction of the protrusions 22 is mostly reflected and / or absorbed by the optical function film 30. Therefore, in the polarizing element of the present invention, the grid structure 20 on which the optical function film 30 described later is formed is provided, so that a single polarized light can be produced. The same polarizing effect can be obtained for light incident from the back side of the substrate 10.
[0024] As shown in FIG. 1(a), the grid structure 20 has a base portion 21. The base portion 21 is a portion provided along the surface of the substrate 10 for supporting the protrusions 22. The base portion 21 is inevitably formed when the uneven shape (protrusions 22) of the grid structure 20 is formed by nanoimprinting or the like. Furthermore, since the base portion 21 is formed in the grid structure 20, the strength of the protrusions 22 can be increased compared to when the protrusions 22 are formed directly on the substrate 10, and therefore the durability of the grid structure 20 can be increased. Furthermore, since the base portion 21 is in close contact with the substrate 10 over the entire surface, the peel resistance of the grid structure 20 can be increased.
[0025] Although there is no particular limitation on the thickness TB of the base portion 21, it is preferably 1 nm or more, and more preferably 10 nm or more, in terms of being able to more reliably support the protrusions 22 and facilitating imprint molding. Also, in terms of ensuring good heat dissipation, the thickness TB of the base portion 21 is preferably 50 μm or less, and more preferably 30 μm or less.
[0026] 1(a) and 1(b), the grid structure 20 has protrusions 22 protruding from the base portion 21. As shown in FIG. 1(b), the protrusions 22 extend in the absorption axis direction or the reflection axis direction of the polarizing element 1 of the present invention as the longitudinal direction, and the presence of a plurality of protrusions 22 forms a lattice shape.
[0027] 1(a) and (b), the formation interval P of the protrusions 22 when observed in a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element 1 must be shorter than the wavelength of light in the band of light used in order to obtain the above-mentioned polarization effect. More specifically, from the viewpoint of achieving both ease of manufacture of the protrusions 22 and polarization properties, the formation interval P of the protrusions 22 is preferably 50 to 300 nm, more preferably 100 to 200 nm, and particularly preferably 100 to 150 nm.
[0028] Furthermore, as shown in Figures 1(a) and (b), the width W of the protrusion 22 when observed in a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element 1 is not particularly limited, but from the viewpoint of achieving both ease of manufacture and polarization characteristics, it is preferably about 20 to 150 nm, and more preferably about 30 to 100 nm. The width W of the protrusions 22 can be measured by observing with a scanning electron microscope or a transmission electron microscope. In the present invention, a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element 1 is observed with a scanning electron microscope or a transmission electron microscope, and the widths at the center positions of the heights H of the protrusions 22 at any four positions are measured, and the arithmetic average value thereof can be regarded as the width W of the protrusions 22.
[0029] Furthermore, as shown in FIG. 1(a), the height H of the protrusion 22 when observed in a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element 1 is not particularly limited, but from the viewpoint of achieving both ease of manufacture and polarization characteristics, it is preferably about 50 to 300 nm, and more preferably about 100 to 250 nm. The height H of the protrusions 22 can be measured by observing with a scanning electron microscope or a transmission electron microscope. In the present invention, a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element 1 is observed using a scanning electron microscope or a transmission electron microscope, and the heights at the center positions of the widths W of the protrusions 22 at any four positions are measured, and the arithmetic average value thereof can be regarded as the height H of the protrusions 22.
[0030] The shape of the protrusions 22 of the grid structure 20 is not particularly limited, except that they protrude from the base portion 21 in a lattice shape in order to obtain polarization characteristics. The shape of the polarizing element 1 when observed in a cross section perpendicular to the absorption axis direction or the reflection axis direction can be, for example, rectangular, trapezoidal, triangular, bell-shaped, etc., as shown in FIG. 2. By having these shapes, the optical function film 30 can be easily formed on the protrusions 22, and the polarizing element 1 can be given polarization properties. In addition, these shapes can be formed by nanoimprinting, which is advantageous in terms of ease of manufacture. In addition, the shape of the recesses formed between the protrusions 22 protruding in a lattice shape of the base part 21 can also be rectangular, trapezoidal, triangular, bell-shaped, etc., as shown in FIG. 25. Among these shapes, the optimal shape can be appropriately selected in consideration of productivity, such as releasability during nanoimprinting.
[0031] The material constituting the grid structure 20 is not particularly limited as long as it is a transparent material, and known organic and inorganic materials can be used. For example, from the viewpoints of ensuring transparency and excellent ease of manufacture, it is preferable to use various types of thermosetting resins, various types of ultraviolet curing resins, glass (spin-on-glass: SOG), etc. as the material for the grid structure 20.
[0032] Furthermore, the material constituting the grid structure 20 can be the same as that of the substrate 10, or a different material can be used. However, from the viewpoints of ease of manufacture and manufacturing costs, it is preferable that the materials constituting the grid structure are different. In addition, when the grid structure 20 and the substrate 10 are made of different materials, the refractive indexes of the two are different, which makes it easy to adjust the refractive index of the entire polarizing element 1.
[0033] The method for forming the grid structure 20 is not particularly limited as long as it is a method capable of forming the above-mentioned base portion 21 and protrusions 22. For example, a method for forming projections and recesses by photolithography or imprinting can be used. Among these, it is preferable to form the base portion 21 and the protrusions 22 of the grid structure 20 by imprinting, since the concave-convex pattern can be formed easily in a short time and the base 21 can be formed reliably.
[0034] When the base portion 21 and the protrusions 22 of the grid structure 20 are formed by the nanoimprinting, for example, a material for forming the grid structure 20 (grid structure material) is applied onto the substrate 10, and then a die having projections and recesses is pressed against the grid structure material, and in this state, ultraviolet light is irradiated or heat is applied to harden the grid structure material. This allows the grid structure 20 having the base portion 21 and the protrusions 22 to be formed.
[0035] (Optical functional film) In embodiment 1 of the polarizing element of the present invention, as shown in FIG. 1(a), the polarizing element further includes an optical function film 30 formed on the protrusions 22 of the grid structure 20, the optical function film 30 being made of an absorbing film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorbing film and the reflective film. The multilayer film 30 can impart desired polarization characteristics to the polarizing element 1 by absorbing and / or reflecting a portion of the incident light.
[0036] The reflective film constituting the optical function film 30 is formed on the protrusions 22 of the grid structure 20 as shown in Figure 1(a), and is therefore able to reflect light incident on the polarizing element 1 that has an electric field component in a direction parallel to the longitudinal direction of the protrusions 22 (the reflection axis direction).
[0037] The material constituting the reflective film is not particularly limited as long as it is a material that has reflectivity for light in the used band, and examples thereof include simple elements such as Al, Ag, Cu, Mo, Cr, Ti, Ni, W, Fe, Si, Ge, and Te, and alloys containing one or more of these elements.
[0038] 1(a), the absorbing film constituting the optical function film 30 is formed on the protrusions 22 of the grid structure 20, and can absorb light having an electric field component in a direction (absorption axis direction) parallel to the longitudinal direction of the protrusions 22 out of the light incident on the polarizing element 1. The absorbed light is converted into heat and dissipated through the substrate 10 described above.
[0039] The material constituting the absorbing film is not particularly limited as long as it is a material that can absorb light in the used band, and examples thereof include dielectric materials and non-dielectric materials.
[0040] Examples of the dielectric material include oxides of elements such as Si, Al, Be, Bi, Ti, Ta, and B; nitrides of elements such as Si and B; fluorides of elements such as Mg and Ca; Si, Ge, carbon, cryolite, and the like. These dielectric materials may be used alone or in combination of two or more. When two or more dielectric materials are used in combination, they may be mixed and used, or different dielectric materials may be used in the film thickness direction.
[0041] The non-dielectric material may be, for example, a simple substance (excluding simple substance Si) or an alloy of at least one element selected from the group consisting of Fe, Ta, Si, Ti, Mg, W, Mo, and Al. Examples of the alloy include an FeSi alloy and a TaSi alloy. From the viewpoints of reflectance and transmittance, the Fe content of the FeSi alloy is preferably 50 atm% or less, more preferably 10 atm% or less. From the viewpoints of reflectance and transmittance, the Ta content of the TaSi alloy is preferably 40 atm% or less. These non-dielectric materials may be used alone or in combination of two or more. When two or more non-dielectric materials are used in combination, two or more non-dielectric materials may be mixed and used, or different non-dielectric materials may be used in the film thickness direction.
[0042] Among these, it is preferable that the dielectric material contains at least one of Si and Si oxide (e.g., silica), and the non-dielectric material contains a metal. Examples of the metal include at least one simple metal selected from the group consisting of Fe, Ta, W, Mo, and Al, or an alloy of the metal. By combining at least one of Si and Si oxide with a metal to form a cermet, the heat resistance of the absorbing film tends to be further improved.
[0043] The content of the non-dielectric material in the absorbing film can also be changed in the film thickness direction. Such a change tends to improve the optical characteristics of the polarizing element 1. By adjusting the change in the content of the non-dielectric material, the wavelength at the minimum point of the absorption axis reflectance Rs can be adjusted.
[0044] The multilayer film constituting the optical function film 30 is a film including at least both the reflective film and the absorbing film described above. By using a multilayer film as the optical function film 30, there are two actions of reflecting light by the reflective film and absorbing light by the absorbing film, and it is possible to obtain more excellent polarization characteristics.
[0045] The multilayer film may have a two-layer structure consisting of the reflective film and the absorbing film, or may have a three-layer structure further including a dielectric film between the reflective film and the absorbing film. In the case where the dielectric film is provided, the dielectric film is preferably formed to a thickness that allows the incident light to pass through the absorbing film and the phase of the polarized light reflected by the reflecting film to be shifted by half a wavelength. A specific thickness is appropriately set within a range of 1 to 500 nm that allows the phase of the polarized light to be adjusted and the interference effect to be enhanced.
[0046] The dielectric film may be made of a common material such as SiO2, Al2O3, or MgF2. The refractive index of the dielectric film is preferably greater than 1.0 and less than or equal to 2.5. The optical properties of the absorbing film are also affected by the refractive index of the surroundings, so the polarization properties may be controlled by the material of the dielectric film.
[0047] It is preferable that the optical function film 30 is formed at least on the tip of the protrusion 22 as shown in FIG. This is because, by forming the optical function film 30 on the tip of the protrusion 22, the above-mentioned light reflection and light absorption functions can be more reliably exerted, and the polarization performance of the entire polarizing element 1 can be further improved.
[0048] 3, it is preferable that the optical function film 30 is not formed on the base portion 21. If the optical function film 30 is formed on the base portion 21, it may impede the transmission of light, which may cause a deterioration in the polarization characteristics of the polarizing element 1.
[0049] Here, in order to form the optical function film 30 not on the base portion 21 of the grid structure 20 but on the tips of the protrusions 22, it is preferable to perform sputtering or deposition of the optical function film 30 from an oblique direction with respect to the protrusions 22 of the grid structure 20 as shown in Fig. 3. This allows the optical function film 30 to be formed only on the tips of the protrusions 22. The angle θ of sputtering or deposition for forming the optical function film 30 is specifically set to about 5 to 70° with respect to the surface of the substrate 10.
[0050] In this way, by forming the optical function film 30 by sputtering or vapor deposition after forming the grid structure 20 made of a transparent material, the film formation conditions, materials, and film thickness can be easily changed. In addition, since the optical function film 30 can be easily adapted to a multi-layer film, a film design utilizing an interference effect can be achieved by combining metals, semiconductors, and dielectrics, and there is no need to consider the material composition that can be etched when forming the optical function film 30, as in the conventional technology. This makes it easy to adjust the absorption rate (attenuation amount) of polarized waves parallel to the grid structure 20 and to adjust the transmittance (transmission amount) of polarized waves perpendicular to the grid structure 20. In addition, by forming the optical function film 30 after forming the grid structure 20, no equipment such as a vacuum dry etching device is required, and there is no need to prepare safety devices such as gases and detoxification devices that are compatible with complicated processes and etching materials, so that running costs such as capital investment and maintenance can be reduced, and cost benefits can be obtained.
[0051] Regarding the state in which the optical function film 30 is formed, for example, as shown in FIG. 3, the optical function film 30 can be formed only on the tips of the protrusions 22 of the grid structure 20. Furthermore, as shown in FIG. 4, when the optical function film 30 is formed by sputtering from an oblique direction relative to the protrusion 22 of the grid structure 20, a large portion of the optical function film 30 protrudes from the tip of the protrusion 22 on the side of the sputtering irradiation source. Furthermore, as shown in FIG. 5, the optical function film 30 may be formed so as to protrude so as to cover not only the tips of the protrusions 22 of the grid structure 20 but also part of the side surfaces.
[0052] From the viewpoint of obtaining better contrast, the optical function film 30 is preferably formed on the tips and parts of the side surfaces of the protrusions 22 of the grid structure 20, as shown in Fig. 5 and Fig. 26. By covering not only the tips but also the side surfaces of the protrusions 22 with the optical function film 30, the absorption performance and / or reflection performance of the polarizing element is improved, and as a result, better contrast is obtained. As a condition for forming the optical function film 30, for example, as shown in FIG. 26, the optical function film 30 can be formed on the tips and parts of the sides of the protrusions 22 of the grid structure 20 by alternately performing sputtering or deposition on the protrusions 22 of the grid structure 20 from multiple directions.
[0053] In addition, when the optical function film 30 is formed on the tip and side of the protrusion 22, it is preferable that it is not formed on the base portion 21 of the grid structure 20. This is to maintain excellent transmittance. Also, as shown in Fig. 4, the optical function film 30 may be formed on only one side of the protrusion 22 when viewed in a cross section perpendicular to the absorption axis direction or reflection axis direction of the polarizing element, but it is preferable that it is formed so as to cover both side surfaces of the protrusion 22 from the viewpoint of obtaining better polarization characteristics regardless of the direction of incident light.
[0054] Furthermore, it is more preferable that the optical function film 30 formed on a part of the side surface of the protrusion 22 is formed in a range covering 10% or more of the height H of the protrusion 22 (HX: height range where the optical function film covers the protrusion ÷ H: height of the protrusion × 100% ≧ 10%) as shown in Fig. 26. This is because by having the optical function film 30 cover 10% or more of the height H of the protrusion, even better contrast can be realized.
[0055] The thickness of the optical function film 30 is not particularly limited, and can be appropriately changed depending on the shape of the grid structure 20, the performance required for the optical function film 30, and the like. For example, when the optical function film 30 is an absorbing film, the thickness can be 5 to 100 nm. When the optical function film 30 is a reflective film, the thickness can be 5 to 200 nm. When the optical function film 30 is a multi-layer film, the thickness can be 10 to 400 nm.
[0056] (Other materials) The polarizing element according to the first embodiment of the present invention may further include members other than the substrate 10, the grid structure 20, and the optically functional film 30 described above.
[0057] For example, in the first embodiment of the polarizing element of the present invention, it is preferable to further include a protective film 40 formed so as to cover at least the surface of the optical function film 30, as shown in FIGS. 6(a) and (b). By forming the protective film 40, the scratch resistance, dirt resistance, and waterproof properties of the polarizing element can be further improved.
[0058] Moreover, it is more preferable that the protective film 40 further includes a water-repellent coating or an oil-repellent coating, since this can further improve the stain-proofing and waterproofing properties of the polarizing element.
[0059] The material constituting the protective film 40 is not particularly limited as long as it can enhance the scratch resistance, dirt resistance, and waterproof properties of the polarizing element. For example, a film made of a dielectric material can be mentioned, and more specifically, an inorganic oxide, a silane-based water-repellent material, etc. The inorganic oxide can be Si oxide, Hf oxide, etc., and the silane-based water-repellent material can be one containing a fluorine-based silane compound such as perfluorodecyltriethoxysilane (FDTS) or one containing a non-fluorine-based silane compound such as octadecyltrichlorosilane (OTS). Among these materials, it is more preferable that the protective film 40 contains at least one of the inorganic oxide and the fluorine-based water-repellent material. When the protective film 40 contains the inorganic oxide, the scratch resistance of the polarizing element can be further improved, and when the protective film 40 contains the fluorine-based water-repellent material, the stain resistance and waterproofing of the polarizing element can be further improved.
[0060] The protective film 40 may be formed so as to cover at least the surface of the optical function film 30, and is more preferably formed so as to cover the surfaces of the grid structure 20 and the optical function film 30, as shown in Fig. 6(a). Also, as shown in Fig. 6(b), the protective film 40 may be formed so as to cover the entire polarizing element 1.
[0061] Furthermore, in the polarizing element according to the first embodiment of the present invention, as shown in Fig. 7, it is preferable that a heat dissipation member 50 is provided so as to cover the substrate 10. This is because the heat from the substrate 10 can be dissipated more efficiently. Here, the heat dissipation member 50 is not particularly limited as long as it has a high heat dissipation effect, and examples thereof include a heat radiator, a heat sink, a heat spreader, a die pad, a heat pipe, a metal cover, and a housing.
[0062] Here, FIG. 8 is a magnified photograph taken with a scanning electron microscope (SEM) of the polarizing element of the present invention that was actually produced. It can be seen from Fig. 8(a) that a grid structure 20 having lattice-shaped protrusions 22 is formed on the substrate 10. It can also be seen from Figs. 8(b) and (c) that the grid structure 20 has a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding from the base portion 21. It can also be seen from Fig. 8(d) that an optical function film 30 made of an absorbing film is formed on the tip of the protrusions 22.
[0063] <Method of manufacturing polarizing element> Next, a method for producing the polarizing element of the present invention will be described. As shown in Figs. 9(a) to 9(d), the method for producing a polarizing element of the present invention includes the steps of forming a grid structure material 23 made of a transparent material on a substrate 10 made of an inorganic material (Fig. 9(a)); A process of forming a grid structure 20 having a base portion 21 provided along the surface of the substrate 10 and protrusion portions 22 protruding in a grid pattern from the base portion 21 (FIG. 9(c)) by performing nanoimprinting on the grid structure material 23 (FIG. 9(b)); The method is characterized by comprising a step of forming an optical function film 30 consisting of an absorptive film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorptive film and the reflective film on the protrusion portion 22 (Figure 9(d)). By going through the above-mentioned steps, it is possible to manufacture the polarizing element 1 having excellent polarization characteristics and heat dissipation properties, without incurring high costs or complicated manufacturing processes.
[0064] On the other hand, in a conventional method for manufacturing a wire grid polarizer, as shown in Figs. 10(a) to (e), in order to produce a convex grid shape, a metal film 80 such as aluminum is formed on a substrate 10 made of an inorganic material such as glass by sputtering or vapor deposition, and an optical functional film material layer 31 made of a material that absorbs light in the used band is formed on the metal film 80 by sputtering or vapor deposition (Fig. 10(a)). Then, a resist mask 70 is patterned using a photolithography technique (Fig. 10(b)). Then, the optical functional film material layer 31 and the metal film 80 are etched by a vacuum dry etching device or the like to form a convex shape made of the metal film 80 and the optical functional film 30 (Fig. 10(c)). For example, if the etching selectivity between the resist mask 70 and the optical functional film material layer 31 / metal film 80 cannot be obtained at this time, an oxide film such as SiO2 is further formed on the optical functional film material layer 31 by sputtering or the like, and a resist mask 70 is formed on the oxide film by photolithography. Thereafter, the resist mask 70 is peeled off (FIG. 10(d)), and then a SiO2 film or the like is formed as a protective film 40 by CVD or the like, and a water- and oil-repellent coating process is also performed as necessary. Although Fig. 10(a)-(e) shows the process for fabricating an absorptive wire-grid polarizer with a basic configuration, a more complicated process is required when a dielectric film such as SiO2 is interposed between the metal film and the absorbing film, or when the absorbing layer is a multi-layer film. Therefore, it can be expected that the conventional wire-grid polarizer fabricated by the process shown in Fig. 10(a)-(e) will be expensive due to the high manufacturing costs and time. In addition, when mass-producing polarizers, it is necessary to prepare multiple high-precision and expensive etching devices and photolithography devices to form convex shapes smaller than the wavelength of light according to the production volume, and it is expected that the capital investment will also be high.
[0065] The substrate 10 made of an inorganic material and used in the method for producing a polarizing element of the present invention may be the same as the substrate 10 described in the above-mentioned polarizing element of the present invention.
[0066] Furthermore, in the manufacturing method of the polarizing element of the present invention, the grid structure material 23 formed on the substrate 10 can be the same as the material used in the grid structure 20 described in the polarizing element of the present invention described above.
[0067] Furthermore, the thickness of the grid structure material 23 can be appropriately adjusted according to the dimensions of the base portion 21 and the protrusions 22 of the grid structure 20 formed by nanoimprinting.
[0068] In the method for producing a polarizing element of the present invention, nanoimprinting is performed on the grid structure material 23 (FIG. 9(b)), but the conditions for nanoimprinting are not particularly limited. For example, as shown in FIG. 9(b), a replica master (or a main master) is used to perform nanoimprinting, and the grid structure material 23 is irradiated with UV light or heated, etc., so as to harden it in the imprinted state. The replica master is then released, whereby a grid structure 20 having a base portion 21 and protrusion portions 22 formed thereon can be transfer-molded.
[0069] The master used in the nanoimprinting can be produced by photolithography, for example, as shown in FIGS. 11(a) to (e). First, a master metal film 62 is formed on a master substrate 61 (FIG. 11(a)), a resist mask 70 is formed (FIG. 11(b)), and the master metal film 62 is etched (FIG. 11(c)). After etching, the resist mask 70 is peeled off to obtain a master 60 including the master substrate 61 and master projections 63 (FIG. 11(d)). Furthermore, the master 60 may further include a release film coat 64, if necessary (FIG. 11(e)). By including the release film coat 64, release can be more easily performed after nanoimprinting the grid structure material 23 (FIG. 9(b)).
[0070] Furthermore, in the manufacturing method of the polarizing element of the present invention, the form of the optically functional film 30 formed on the protrusion portion 22 can be the same as that of the optically functional film 30 described in the polarizing element of the present invention described above.
[0071] In addition, in the manufacturing method of the polarizing element of the present invention, as necessary, a protective film 40 may be further formed so as to cover the surfaces of the grid structure 20 and the optical function film 30, as shown in Figure 9(d). The protective film may be formed in the same manner as the protective film 40 described above in relation to the polarizing element of the present invention.
[0072] <Head-up display device> Next, an embodiment of the head-up display device of the present invention will be described. As shown in FIG. 12, a head-up display device according to an embodiment 100 of the present invention includes the above-described polarizing element 1 of the present invention. By providing the head-up display device 100 with the polarizing element 1 of the present invention, it is possible to improve the polarization characteristics and heat resistance. Head-up displays incorporating conventional polarizing elements have poor heat dissipation properties, and are therefore considered to have insufficient heat resistance when considering long-term use and future needs for higher brightness and enlarged display.
[0073] In addition, in the embodiment 100 of the head-up display device of the present invention, there is no particular limitation on the position of the polarizing element 1. For example, as shown in Fig. 12, a light source 2, a display element 3 that emits a display image, and a reflector 4 that reflects the display image to a display surface 5 may be provided, and the polarizing element 1 may be provided between the display element 3 and the reflector 4. By using the polarizing element 1 of the present invention as a pre-polarizing plate placed in front of the display element 3, it is possible to transmit the display image emitted from the display element 3 while suppressing sunlight from entering the display element 3, thereby further improving the heat resistance and durability of the head-up display.
[0074] In the embodiment 100 of the head-up display device of the present invention, as shown in Fig. 12, the display element 3 is, for example, a transmissive liquid crystal panel in which liquid crystal is sealed between a pair of substrates transparent to light in the used band, and polarizing elements (not shown) are attached to the front and back of the display element 3. The polarization axes of the front and rear polarizing elements attached to the display element 3 are perpendicular to each other. A light source 2 such as an LED is arranged behind the display element 3 (on the opposite side to the emission direction of the display image), and the display element 3 can be illuminated to emit the display image. The polarizing element 1, which is arranged on the front side of the display element 3 (forward in the emission direction of the display image), is arranged so that its polarization axis is in the same direction as the polarizing element attached to the front side of the display element 3, and transmits the display image emitted from the display element 3. The display image transmitted through the polarizing element 1 is reflected by a mirror (reflector 4) arranged at an angle of approximately 45° to the display element 3, and is emitted onto the windshield surface (display surface 5), so that the display image is visually recognized as a virtual image by the driver (person). Each of these components that make up the head-up display device is stored in a housing.
[0075] Furthermore, in the embodiment 100 of the head-up display device of the present invention, as shown in Fig. 13, it is preferable that a heat dissipation member 50 is provided around the polarizing element 1. This is because it is possible to more efficiently release heat from the polarizing element 1 and further improve the heat resistance of the device. Here, the heat dissipation member 50 is the same as the heat dissipation member 50 described in the above-mentioned polarizing element 1 of the present invention.
[0076] It should be noted that the configuration of the head-up display device 100 shown in Figures 12 and 13 is a minimum and basic configuration, and each component constituting the head-up display device of the present invention is not limited to those shown in Figures 12 and 13, and other components may be provided as appropriate depending on the required performance, etc.
[0077] In addition, in the head-up display device of the present invention, as described above, the position of the polarizing element 1 is not particularly limited, and can be selected as appropriate depending on the configuration of the head-up display device and the required performance. For example, although not shown, the polarizing element 1 can be provided between the display element 3 and the light source 2 . Although not shown, the polarizing element 1 can also be incorporated into the reflector 4 . Furthermore, the cover portion 6 provided in the head-up display device can also be formed from the polarizing element 1. EXAMPLES
[0078] The present invention will now be described in detail with reference to examples, although the present invention is not limited to the following examples in any way.
[0079] <Example 1> As shown in Figure 6(b), a model of a polarizing element 1 was created, which includes a substrate 10 made of glass, a grid structure 20 made of ultraviolet-curable resin (acrylic resin) and having a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding in a grid pattern from the base portion 21, an optically functional film 30 made of a Ge absorbing film that absorbs light and formed on the protrusions 22, and a protective film 40 made of SiO2. Then, for the manufactured polarizing element 1 model, the conditions of the grid structure 20 and the optical function film 30 were changed as shown in (1) to (9) below, and the optical characteristics (transmission axis transmittance: Tp, absorption axis transmittance: Ts, transmission axis reflectance: Rp, absorption axis reflectance: Rs, contrast: CR) for light with wavelengths of 430 to 680 nm were evaluated. The optical properties of the fabricated model were verified by electromagnetic field simulation using the Rigorous Coupled Wave Analysis (RCWA) method. The simulation was performed using the grating simulator Gsolver by Grating Solver Development, Inc.
[0080] (1) Type of material for grid structure For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the material of the grid structure 20 was SiO2 made of SOG and when it was polymethyl methacrylate resin (PMMA), which is an ultraviolet curable resin. The comparison results are shown in FIG.
[0081] 14, it was confirmed that equivalent characteristics were obtained when the grid structure 20 was made of SiO2 or PMMA. This result shows that by forming the grid structure 20 from a material transparent to light in the used band, equivalent characteristics can be obtained whether the material is an inorganic material or an organic material, making it possible to select an appropriate material in consideration of the required characteristics, reliability, and mass productivity.
[0082] (2) Thickness of the base of the grid structure For the model of the polarizing element 1, average values of optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the thickness TB of the base portion 21 of the grid structure 20 was changed. The comparison results are shown in FIG.
[0083] From the results in Fig. 15, it was confirmed that the thickness TB of the base portion 21 was changed at regular intervals from 0 nm to 30,000 nm, and changing the thickness of the base portion 21 had little effect on the polarization characteristics. However, it was found that the characteristics of Tp and Ts change when the thickness of the base portion 21 exceeds 30,000 nm (30 µm). From these results, it is understood that the thickness of the base portion 21 can be appropriately adjusted within a certain range according to reliability including adhesion, and that there is no need for strict process management such as management of the base layer in the mass production process, resulting in cost benefits.
[0084] (3) Height of protrusions of grid structure For the model of the polarizing element 1, average values of optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the height H of the protrusions 22 of the grid structure 20 protruding from the base portion 21 was changed. The comparison results are shown in FIG.
[0085] 16, it was confirmed that the height of the protrusions 22 was changed at certain intervals from 20 nm to 400 nm, but there was almost no effect on the polarization characteristics. From this result, it can be seen that by forming the protrusions 22 from a material transparent to the light in the used band, strict process management such as management of the height H of the protrusions 22 is not necessary, and when considering mass productivity, it is easier to manufacture the protrusions 22 when the height H is lower, which is also advantageous when considering yield and reliability.
[0086] (4) Thickness of the absorbing film For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the thickness of the absorbing film as the optical function film 30 (the film thickness of the thickest part of the absorbing film attached to the protrusion 22) was changed. The comparison results are shown in FIG.
[0087] From the results of Fig. 17, it was confirmed that the polarization characteristics change when the thickness of the absorbing film is changed at certain intervals from 10 nm to 50 nm. Therefore, it is understood that the optical characteristics, particularly Rs and Ts, can be controlled by forming an absorbing film after forming the grid structure 20 from a material transparent to light in the used band and controlling the thickness of this absorbing film, and thus it is possible to optimize the polarization characteristics to meet the needs of the customer by controlling only the thickness of the absorbing film.
[0088] (5) Type of absorbent membrane material For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when Ge was used and when FeSi was used as the material of the absorbing film as the optical function film 30. The comparison results are shown in FIG.
[0089] From the results of FIG. 18, it was confirmed that the polarization characteristics change by changing the type of material of the absorbing film. Therefore, after forming the grid structure 20 with a material transparent to the light in the used band, the absorbing film is formed, and by changing the type of this absorbing film, the optical characteristics, particularly Rs and Ts, can be controlled, and it can be seen that the polarization characteristics can be optimized by selecting the material of the absorbing film to meet the needs of the customer. In addition, it is possible to utilize the interference effect by forming a multilayer structure combining metals, semiconductors, and dielectrics, and it can be inferred that the polarization characteristics can be further optimized.
[0090] (6) Width of the absorbing film For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) were plotted and compared when the width parallel to the transmission axis of the incident light of the optical function film 30 formed on each protrusion 21 of the grid structure 20 (i.e., the width in the direction perpendicular to the longitudinal direction of the grid structure) was changed. The comparison results are shown in FIG.
[0091] From the results of Fig. 19, it was confirmed that the polarization characteristics change by changing the width of the absorbing film. Therefore, after forming the grid structure 20 with a material transparent to the light in the used band, the absorbing film is formed, and by changing the width of the absorbing film, the optical characteristics, particularly Rs, Rp, and Tp, can be controlled, and it can be seen that the polarization characteristics can be optimized by selecting the material of the absorbing film according to the needs of the customer.
[0092] (7) Formation state of the absorbing film For the model of polarizing element 1, the average values of the optical properties (Tp, Rp, Ts, Rs, CR) were plotted and compared when the formation state was changed to a case where an absorbing film was formed only on the tip of the protrusion 22 as shown in Fig. 3, a case where an absorbing film was formed thickly on one side of the tip of the protrusion 22 as shown in Fig. 4, and a case where an absorbing film was formed thickly on both sides of the tip of the protrusion 22 as shown in Fig. 5. The comparison results are shown in Fig. 20.
[0093] 20, it was confirmed that the polarization characteristics change when the way the absorbing film is attached to each protrusion 21 of the grid structure 20 is changed. Therefore, it is understood that the optical characteristics, particularly Rs and Ts, can be controlled by changing the angle θ of the oblique sputtering or by performing sputtering from both sides, enabling optimization according to the polarization characteristics required by the customer.
[0094] 17 to 20, it can be seen that by forming the grid structure 20 out of a material transparent to the light in the used band and forming an absorbing film thereon, and controlling the method of forming the absorbing film (material, thickness, film width, state of formation on the tip of the protrusion, etc.), it is possible to adjust the polarization characteristics to meet customer needs. Similarly, it can be seen that the desired polarization characteristics can be obtained by forming and controlling a reflective film or a multilayer film.
[0095] (8) Thickness of the reflective film For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the thickness of the reflective film as the optical function film 30 (the film thickness of the thickest part of the reflective film attached to the protrusion 22) was changed. The comparison results are shown in FIG.
[0096] From the results of Fig. 21, it was confirmed that the polarization characteristics change when the thickness of the reflective film is changed at certain intervals from 30 nm to 100 nm. Therefore, it is understood that the optical characteristics, particularly Rs and Ts, can be controlled by forming a reflective film after forming the grid structure 20 from a material transparent to light in the used band and controlling the thickness of this reflective film, and thus it is possible to optimize the polarization characteristics to meet the needs of the customer by controlling only the thickness of the reflective film.
[0097] (9) Height range where the reflective film covers the protrusion For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the range of the reflective film formed on the tip and side of the protrusion 22 as the optical function film 30 covering the protrusion 22 (the ratio (%) of the height range HX covered by the optical function film to the height H of the protrusion) was changed. Of the comparison results, Tp, Rp, Ts, and Rs are shown in Figure 27(a), and the contrast is shown in Figure 27(b). From the results in FIG. 27, it was found that the contrast characteristics can be improved while maintaining good optical characteristics when the ratio (HX / H) of the reflective film covering the protrusion side surface of the protrusion 22 is increased. In FIG. 27(b), the CR characteristics are further improved when the ratio of the reflective film covering the protrusion side surface of the protrusion 22 is increased to 60%, 76%, and 92%. Therefore, it is found that the optical characteristics, especially the contrast, can be controlled by forming the optical function film 30 after forming the grid structure 20 from a material transparent to light in the used band, and controlling the film formation range of the optical function film 30 on the side surface of the protrusion 22 of the grid structure 20, and thus it is possible to realize polarization characteristics that meet the needs of the customer. (It is not formed on the base portion 21. If even a part of the optical function film 30 is formed on the base portion 21, the Tp characteristic will deteriorate.)
[0098] (10) Types of optical functional films For the model of the polarizing element 1, the average values of the optical characteristics (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm were plotted and compared when the combination of the absorbing film, the reflective film, and the dielectric film as the optical function film 30 was changed. The comparison results are shown in FIG. 22(a). In FIG. 22(a), "Ge" indicates that the optical function film 30 is made of a Ge absorbing film, "Al100" indicates that the optical function film 30 is made of an Al reflective film having a thickness of 100 nm, "Ge / Al" indicates that the optical function film 30 is a laminate of a Ge absorbing film and an Al reflective film having a thickness of 100 nm, and "Ge / SiO2_10 / Al50" indicates that the optical function film 30 is a laminate of a Ge absorbing film, a dielectric film made of SiO2 having a thickness of 10 nm, and an Al reflective film having a thickness of 50 nm. FIG. 22(b) shows only the CR results among the optical characteristics shown in FIG. 22(a).
[0099] From the results in Figure 22(a), it is clear that Rs can be controlled by selecting and depositing the type of optically functional film, such as an absorbing film (Ge) or a reflective film (Al), according to the purpose, and that it is possible to fabricate either an absorptive polarizing element or a reflective polarizing element. It is also clear that by laminating a reflective film (Al) and an absorptive film (Ge), it is possible to provide an absorptive polarizing element with even lower Rs than the absorptive film alone. Furthermore, from the results in Figures 22(a) and (b), it can be seen that the combination of reflective film (Al) / dielectric film (SiO2) / absorbing film (Ge) can maintain polarization characteristics equivalent to that of a two-layer structure of a reflective film and an absorbing film, while improving contrast as shown in the result in Figure 22(b). In this way, the polarization characteristics can be optimized by configuring the optically functional film to meet customer needs.
[0100] <Example 2> As shown in Figure 6 (b), a sample of a polarizing element 1 was actually produced, which includes a substrate 10 made of glass, a grid structure 20 made of ultraviolet-curable resin (acrylic resin) and having a base portion 21 provided along the surface of the substrate 10 and protrusions 22 protruding in a grid pattern from the base portion 21, an optically functional film 30 made of a Ge absorbing film that absorbs light and formed on the protrusions 22, and a protective film 40 made of Al2O3. The prepared polarizing element 1 sample was subjected to the following tests (1) and (2).
[0101] (1) Observation of the grid structure of the fabricated sample Here, FIGS. 23(a) and (b) are enlarged photographs taken with a scanning electron microscope (SEM) of a cross section of an actually produced polarizing element of the present invention. 23(a) and (b), the grid structure 20 is formed with a base portion 21 provided along the surface of the substrate 10 and protruding portions 22 protruding from the base portion 21. Also, from FIG. 23(b), it is understood that an optical function film 30 made of an absorbing film is formed on the tip of the protruding portion 22. It is also understood that a protective film 40 is formed so as to cover the base portion 21, the protruding portions 22 protruding from the base portion 21, the optical function film 30 made of an absorbing film on the tip of the protruding portion 22, and all of these. Note that this protective film 40 was formed using the ALD (Atomic Layer Deposition) film formation method, and was formed to a thickness of 8 nm using Al2O3 as the material.
[0102] (2) Heat resistance of the prepared samples A high temperature test was carried out on the produced sample of polarizing element 1. The high temperature test was carried out under the condition that the sample was left at 150° C. for 800 hours. FIG. 24 plots and compares the average values of the optical properties (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm before the high-temperature test and the average values of the optical properties (Tp, Rp, Ts, Rs, CR) for wavelengths of 430 to 680 nm after the high-temperature test (150°C, after 800 hours).
[0103] 24, it was confirmed that the polarization characteristics of the polarizing element of the present invention do not change significantly even when left in a high-temperature environment of 150° C. for 800 hours. Therefore, it can be used safely in the temperature environment required for in-vehicle devices, and it is clear that it is possible to provide polarizing elements that meet customer needs. [Industrial Applicability]
[0104] According to the present invention, it is possible to provide a polarizing element having good polarization characteristics, excellent heat dissipation properties, and a manufacturing method for a polarizing element, which is low in manufacturing cost. Also, according to the present invention, it is possible to provide a head-up display device having excellent polarization characteristics and heat resistance. [Explanation of symbols]
[0105] 1 Polarizing element 2 light source 3. Display element 4 reflector 5 Display surface 6 Cover part 10 Substrate 20 Grid Structure 21 Base 22 Protrusion 23 Grid structure materials 30 Optical functional film 31 Optical functional film material layer 40 Protective film 50 Heat dissipation material 60 Master 61 Master Substrate 62 Metal film for master 63 Master plate protrusion 64 Release film coating 70 Resist Mask 80 Metal Film 100 Head-up display device
Claims
1. A substrate made of a transparent inorganic material; a grid structure made of a transparent material and having a base portion having a thickness of 30 μm or less provided along a surface of the substrate and protrusions protruding in a grid shape from the base portion; an optical function film formed on the protrusion and made of a multilayer film having at least an absorbing film that absorbs light and a reflective film that reflects light; Equipped with the optical function film is formed on the tip and part of the side of the protrusion, and covers 60% or more of the height of the protrusion; the optical function film is a multi-layer film having a two-layer structure of the reflective film and the absorbing film, or a three-layer structure of the reflective film, the absorbing film, and a dielectric film; A polarizing element comprising:
2. 2. The polarizing element according to claim 1, wherein the base portion has a thickness of 1 nm or more.
3. 3. The polarizing element according to claim 1, wherein the shape of the protrusion when viewed in a cross section perpendicular to the absorption axis direction or the reflection axis direction of the polarizing element is rectangular, trapezoidal, polygonal, or elliptical.
4. 4. The polarizing element according to claim 1, wherein the optically functional film is not formed on the base portion.
5. 5. The polarizing element according to claim 1, wherein the inorganic material constituting the substrate is different from the material constituting the grid structure.
6. 6. The polarizing element according to claim 1, further comprising a protective film formed so as to cover at least a surface of the optically functional film.
7. The polarizing element according to claim 6 , wherein the protective film includes a water-repellent coating or an oil-repellent coating.
8. forming a grid structure material made of a transparent material on a substrate made of an inorganic material; forming a grid structure having a base portion having a thickness of 30 μm or less provided along a surface of a substrate and protrusion portions protruding in a grid pattern from the base portion by performing nanoimprinting on the grid structure material; forming, on the protrusions, an optically functional film made of an absorbing film that absorbs light, a reflective film that reflects light, or a multilayer film having at least the absorbing film and the reflective film, The optical function film is formed on the tip and part of the side of the protrusion so as to cover 60% or more of the height of the protrusion, A method for manufacturing a polarizing element, wherein the optically functional film is a multi-layer film having a two-layer structure of the reflective film and the absorbing film, or a three-layer structure of the reflective film and the absorbing film.
9. 9. The method for producing a polarizing element according to claim 8, wherein the step of forming the optically functional film comprises forming films alternately from a plurality of directions on the protrusions by sputtering or vapor deposition.
10. A head-up display device comprising the polarizing element according to any one of claims 1 to 7.
11. The head-up display device according to claim 10, further comprising a heat dissipation member provided around the polarizing element.
Citation Information
Patent Citations
Polarized light separating element and manufacturing method thereof
JP2006003447A
Wire grid polarizer and liquid display device using the same
JP2008083657A
Reflection type polarizer and liquid crystal display device
JP2008181113A
Method for manufacturing wire grid polarizer
JP2011227130A
Video display system, and setting method of video display device
JP2015007763A